Biomechanics of Copenhagen Adduction Exercise and Eccentric Hip Adductor Exercises on a Novel Isokinetic Dynamometer With Within‐Session Repeatability - J. Marušič; O. Cvjetičanin; M. Supej; J. Babič; N. Šarabon (Scandinavian Journal of Medicine & Science in Sports, 2026)
ABSTRACT This study biomechanically evaluated the eccentric phase of short and long lever Copenhagen adduction exercise (CAE) and compared them with unilateral and bilateral eccentric hip adductor exercises performed on a novel eccentric hip adductor dynamometer (EHAD). Fifteen participants completed two CAE variations and five EHAD exercises. Three‐dimensional kinematics and force data were collected to compute peak hip joint torque, range of motion (ROM), and angle at peak torque as the primary dependent variables. Peak and mean external force and body‐mass‐normalized torque were reported. Effects of exercise type and lever length on primary dependent variables, as well as relative and absolute within‐session repeatability, were evaluated. The CAE produced significantly lower peak eccentric torques than all EHAD variations, regardless of lever length or unilateral/bilateral performance. Long lever CAE elicited greater peak and average torques than the short lever CAE, although ROM was significantly lower in the long lever condition across exercises. EHAD exercises generated significantly greater peak torques during bilateral performance, demonstrating the presence of bilateral facilitation (27.9% ± 16.5%). Angle at peak torque was similar across all exercises (31°–39°). With the exception of angle at peak torque during the CAE, all measurements showed good to excellent relative and moderate to good absolute within‐session repeatability. Increasing lever length during CAE effectively raises hip adductor loading, while all EHAD variations enable even greater loading and exhibit pronounced bilateral facilitation. Future intervention studies should determine whether these biomechanical advantages translate into clinically meaningful improvements in adductor‐related groin injury prevention and rehabilitation outcomes.